(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article talks about mental development and behavioral characteristics during elementary school age. If the child’s cognitive processes are strained by teaching the child to read, write, and count early, it causes a shortage of brain power, which is necessary for the child’s emotional and emotional development, children ’s emotional emotional processes or physical defects occur in development.